Communication, culture and cyberspace: Analysis on the educational role of the folkloric project Cordel Animado! (Revista Internacional de Folkcomunicação, 2019)
The present work aimed to analyze how the Cordel Animado! contributes to the education of children, from a popular northeastern media, the cordel, linked to a global media, the internet, generating a folkmidiático product. The project studied, written by Mariane Bigio and Milla Bigio from Pernambuco, has been published since 2014 through a personal blog and a YouTube channel. In them are written narratives of children's cords and educational stuff built with music, sound and theatrical interpretation. To make the research, we use as main theoretical bases the Theory of Folkcommunication, Educommunication and Popular Education. The qualitative methodology was configured in the stages of bibliographic research, as well as in the analysis and observation of the educational and communicational practices of the contents available on the internet. From this theoretical-methodological contribution, we conclude that the political-pedagogical project of Cordel Animado! is based on democratic, inclusive and popular principles, fostering children's citizenship education. Cordel; Education; Folkommunication; Culture; Citizenship.